R-Loop Tracker: Web Access-Based Tool for R-Loop Detection and Analysis in Genomic DNA Sequences - Brázda, Václav; Havlík, Jan; Kolomazník, Jan; Trenz, Oldřich; Šťastný, Jiří (International journal of molecular sciences, 2021)
R-loops are common non-B nucleic acid structures formed by a three-stranded nucleic acid composed of an RNA-DNA hybrid and a displaced single-stranded DNA (ssDNA) loop. Because the aberrant R-loop formation leads to increased mutagenesis, hyper-recombination, rearrangements, and transcription-replication collisions, it is regarded as important in human diseases. Therefore, its prevalence and distribution in genomes are studied intensively. However, in silico tools for R-loop prediction are limited, and therefore, we have developed the R-loop tracker tool, which was implemented as a part of the DNA Analyser web server. This new tool is focused upon (1) prediction of R-loops in genomic DNA without length and sequence limitations; (2) integration of R-loop tracker results with other tools for nucleic acids analyses, including Genome Browser; (3) internal cross-evaluation of in silico results with experimental data, where available; (4) easy export and correlation analyses with other genome features and markers; and (5) enhanced visualization outputs. Our new R-loop tracker tool is freely accessible on the web pages of DNA Analyser tools, and its implementation on the web-based server allows effective analyses not only for DNA segments but also for full chromosomes and genomes.
Keywords: Algorithms; DNA; Internet; Software; R-Loop Structures; software; internet; lidé; Genomics; algoritmy; Genomic Instability; Humans; nestabilita genomu; R-smyčka; genomika